Gender equality legislation and foreign direct investment: Evidence from the labour market of Taiwan ROC. Issue 2 (2nd May 2017) - Lai, Yu-Cheng; Sarkar, Santanu
Abstract : Purpose: The purpose of this paper is to examine the differences in the effects of gender equality legislation on employment outcomes among female and male workers in industries with different intensity of foreign investment (namely, foreign direct investment (FDI)-intensive industries and non–FDI–intensive industries). The specific employment outcomes that were studied to compare the effects of the legislation are the working hours, employment opportunities, and wages of female and male workers in Taiwan. Design/methodology/approach: Using data from the annual Manpower Utilization Survey, the authors applied a differences-in-differences-in-differences estimation method to test the effect of gender equality legislation on employment outcomes. By using multinomial logit, the authors measured the effect of the legislation on employment opportunities. To correct for simultaneity and selectivity problems/biases, the authors adopted Heckman two-stage selection procedures. Likewise, the authors used weighted least squares to solve heteroskedasticity in the wage and working hour equations. Further, the instrumental variable (IV) method was used to correct for simultaneity bias in the equation on working hour. The authors applied three stages estimation method following Killingsworth's (1983) approach to measure the effect of the legislation on wages and working hours. Findings: The authors found the restrictions enforced by the gender equality legislation (namely the Gender Equal Employment Act (GEEA), enacted in 2002) in Taiwan to have made certain impact on the workers' working conditions in FDI-intensive industries. The major finding indicated that in a country like Taiwan, where the legislature tried tilling the perpetual gender gap in its labour market, by passing a law to counter inequality, could finally narrow the gender gap in wages among workers in the FDI-intensive industries. Although initially after the enactment of the GEEA (between 2002 and 2004), the gender gap in part-timers' wages has widened, yet over a period of time the gap in their wages too has narrowed down, particularly during 2005-2006. The legislation, however, could not improve the job opportunities for full-time female workers' in FDI-intensive industries. Besides, post 2002, the female workers were found to have worked for shorter hours than male workers, which according to us, could be largely attributed to the enforcement of the GEEA. Practical implications: An in-depth analysis of the labour market effects of gender equality legislation should be useful to policymakers, especially those interested in understanding the impact of legislative measures and policy reforms on labour market and employment outcomes across industry types. If enforcement of a gender equality legislation has succeeded in reducing the gender gap more in one set of industries than the others (e.g. foreign owned instead of domestic industries), as the authors noticed in this study, then the same should have a bearing on revamping of future enactment and enforcement too. Originality/value: Current study findings would not only provide the broad lessons to the policymakers in Taiwan, but the results that have emerged from a country case study could be referred by other growing economies who are enthusiastic about improving female workers' working conditions through legislative reforms.